Review of Political Theory of Islamic Law Abul 'Ala Al Maududy Positive Perspective of the Political System of Indonesian Islamic Law - Ahmadi Hasan; Salafuddin Noor; Nuril Khasyi'in (Syariah: Jurnal Hukum dan Pemikiran, 2023)
Abstract: Islam is diinullah wa rahmatan lill'aalamiin. The main sources of Islamic law are the Holy Qur'an and AsSunnah-Al Hadith of the Prophet Muhammad. Complete, systematic, and perfect Islamic treatise has been established and developed on its three main fundamental pillars namely aqidah-tauhidullah, sharia-fiqh al-worship mu'amalah, and tasawwuf-akhlaqiyah. The principle of sharia is the principle of Sunnatullah Divineyyah in the construction of Islamic Law which originates from the revelation of Allah SWT. contained in the texts of the Qur'an and Assunnah-Al Hadith of the Prophet Muhammad. In the hands and soul of the fundamentalist revolutionary thought of Abul A'la Al Maududi, the true values and principles of Islamic teachings are applied purely, solidly, and interpretatively, consistently, istiqamah and kaffah, both individually and as a group in diverse, societal, nation and state. Al Islam stands firmly on the principle of monotheism which recognizes and believes in belief in Allah SWT. as the Substance of the Maha Ahad (the unity of godhead) who has the right to be worshiped and worshiped by all His creatures, as has been the guideline and treatise taught from all prophetic and apostolic lineages, since the Prophet Adam As. to the time of the Prophet Muhammad Rasulullah SAW. Al Maududi prioritizes the aspects and implementation of pure Islamic values and principles which concern matters of Allah's sovereignty and rejects the concept of human sovereignty. Allah is the owner and maker of law (sharia) which aims to shape human life which includes matters of political, economic, educational, social, and state activities so that they become better and run according to the rules and guidelines of Islamic sharia. In this way, an atmosphere of justice is created that protects the rights of ownership and the interests of human life, so that a sense of justice, peace, order, prosperity, happiness, safety, and protection of religion, intellect, soul, property and offspring is created for all parties. The focus of Al Maududi's theory and thoughts lies in the idea of developing Islamic politics and the climax will form a pure Islamic State led by an Islamic Caliph who has been legitimized by the will and sovereignty of all Muslims-Muslims. Specifically, this aims to replace and eliminate the domination of ideology and theory by Western thinkers who are considered to be able to lead to the path of disbelief, disobedience, tyranny, and destruction. Meanwhile, the 1945 Constitution of the Republic of Indonesia states that Indonesia is a state based on law (rechtsstaat) not based on mere power (machsstaat). This implies that law must play a very important and decisive role in realizing the ideals of the Indonesian nation, as well as indicating the importance of the political system of Islamic law in the Unitary State of the Republic of Indonesia.Keywords: Al Maududi's Theory, Comparative Perspective, Indonesian Islamic Political Law.